2016
DOI: 10.1049/iet-est.2014.0067
|View full text |Cite
|
Sign up to set email alerts
|

Driver alerting system using range estimation of electric vehicles in real time under dynamically varying environmental conditions

Abstract: , "Driver alerting system using range estimation of electric vehicles in real time under dynamically varying environmental conditions," IET Electrical Systems in Transportation, vol. 6, (2) pp. 107-116, 2016. Driver alerting system using range estimation of electric vehicles in real time under dynamically varying environmental conditions AbstractAs the technology supporting electric vehicles (EVs) is rapidly progressing and the cost of EV components is reducing, EVs are becoming more feasible for use in Aus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 16 publications
0
28
0
Order By: Relevance
“…Based on the transmission system gear ratio and the efficiency, the load power seen from the shaft of the induction motor can be calculated. In the proposed method the efficiency of the drive system (motor plus inverter) is calculated at any instant of time, unlike many papers where the authors consider the efficiency reported by the manufacturer data is assumed to be constant at any instant of time [3] [12]. In order to improve the SoC estimation, auxiliary electric loads such as that used for air conditioning, windscreen wipers and lighting are also taken into account.…”
Section: A Data Collection and Battery Power Calculationmentioning
confidence: 99%
See 4 more Smart Citations
“…Based on the transmission system gear ratio and the efficiency, the load power seen from the shaft of the induction motor can be calculated. In the proposed method the efficiency of the drive system (motor plus inverter) is calculated at any instant of time, unlike many papers where the authors consider the efficiency reported by the manufacturer data is assumed to be constant at any instant of time [3] [12]. In order to improve the SoC estimation, auxiliary electric loads such as that used for air conditioning, windscreen wipers and lighting are also taken into account.…”
Section: A Data Collection and Battery Power Calculationmentioning
confidence: 99%
“…Fig. 4, shows how friction loss, gravity loss, aerodynamic loss and acceleration loss are taken into account during the calculation of the traction power/force [3] [12]. The full details of the traction power calculation along a segment of a route are given in Equations (1) -(3).…”
Section: A Data Collection and Battery Power Calculationmentioning
confidence: 99%
See 3 more Smart Citations